Yawn contagion in bonobos: Another group, another story. Issue 3 (31st January 2022) - Norscia, Ivan; Caselli, Marta; De Meo, Gabriele; Cordoni, Giada; Guéry, Jean‐Pascal; Demuru, Elisa
Abstract: In primates, yawn contagion (the yawning response elicited by others' yawn) is variably influenced by individual (e.g., sex, age) and social factors (e.g., familiarity) and possibly linked to interindividual synchronization, coordination, and emotional contagion. Two out of three studies on yawn contagion in bonobos ( Pan paniscus ), found the presence of the phenomenon with mixed results concerning the effect of familiarity and no replication on its modulating factors. To address this puzzling issue, we recorded all occurrences data on yawn contagion in a captive bonobo group (March–June 2021; 18 individuals; La Vallée des Singes, France). Contrary to chimpanzees and humans, the number of triggering yawns increased contagion, possibly owing to a higher stimulus threshold. This aspect may explain the interindividual variability observed in yawn contagion rates. In subjects under weaning, we did not detect yawn contagion and, as it occurs in certain human cohorts, yawn contagion declined with age, possibly due to reduced sensitivity to others. Females responded more than males and elicited more responses from females when showing sexual swelling. As reproductive females are central in bonobo society, our results support the hypothesis that—as in other Hominini—the most influential sex can influence yawn contagion. The relationship quality (measured via grooming/play) did not affect yawn contagion, possibly due to bonobos' xenophilic nature. Overall, this study confirms the presence of yawn contagion in bonobos and introduces new elements on its modulating factors, pointing toward the necessity of cross‐group studies. Abstract : Influence of modulating factors on the yawn contagion network, indicated via in‐degree prestige based node size. The different quadrants highlight: (top‐right) age classes (<12 years old: white nodes; 12–30 years old: light grey nodes; over 30: dark grey nodes); (top‐left) sex (males: white nodes; females: gray nodes); (bottom‐right) swelling status within the female network (females without swelling: white nodes; females with swelling: grey nodes). Edge arrows (bottom‐left) indicate the direction of contagion between nodes and go from the trigger to the responder.